Dentro del laberinto : salud reproductiva y sociedad - Salles, Vania; Tuirán, Rodolfo (El Colegio de México A.C., 1997)
The purpose of this article is to outline a series of analytical frameworks defined by relevant social structures and processes, in order to explore how some social contexts influence sexual and reproductive behaviors, as well as institucional actions and individual or group practices. The article is intended to shape a theoretical and analytical proposition which may be useful for current research programs on reproductive health, emphasizing how indispensable the social science approach is. We believe that this approach may make significant contributions to the newly-emerging field of reproductive health, such as gaining a more integral and fuller understanding of health/sickness processes, and their determinants and consequences; organizing and situating in a broader context the findings of social, biomedical, and public health research; helping to establish priorities for public policies; and orienting the future agenda of research related to this topic.